(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Based on the recent World Bank urban transport strategy review "Cities on the move", the paper examines the critical differences between the urban transport problems facing cities in the developing and industrialized worlds. Premature congestion and deteriorating environmental safety and security conditions are seen as endemic in the developing country cities. Although the proportion of urban space devoted to movement is often relatively low in the developing world, rates of motorization are seen to be not untypical of those experienced in industrialized countries at similar average income levels. Hence rather than explaining the differences primarily in terms of natural endowments, the paper emphasizes the different and weaker policy and institutional contexts in which urban transport is typically performed in developing countries. It argues that the industrialized world, and particularly the multilateral banks and aid agencies, can make their most effective contribution to development by concentrating on assisting developing countries to overcome these institutional impediments to successful urban development.